Posture Instability of People Diagnosed with Parkinson’s Disease A Review - Ravi, T; Ranganathan, Rajesh; Sivasankar, A (International Journal of Engineering and Technology, 2018)
The intent of the paper is to ascertain the reasons behind the posture instability which is being the most disabling feature encountered by the people diseased with Parkinson’s which interns leads to risk of fall there by increases the fractures with history of falls. In this paper a literature survey has been carried out to look after the recent inventions/aids in the clinical aspect and mechanical aspects for supporting PD patients to walk freely without Fear of Falling (FOF).